Mindfulness of Death’s Cultivation - Nathapunyo (Karat), Phramaha Boonpasid; Sutthisanmethi, Phra (Journal of Dhamma for Life, 2023)
Death is the unavoidable truth that every living thing must confront. This explains why it is not unexpected that the majority of people are terrified of dying, avoid speaking, avoid hearing, and avoid seeing oneself or those close to them. and had no desire to learn about dying. This results in a lack of knowledge, which breeds despair and a fear of dying. It would increase in size for regular people. Also, it made him sit carelessly and extravagantly, relishing his own small pleasures. It disregards the significance of time, age, and the absence of disease, for instance, forgetting that everyone will eventually pass away. Individuals should regularly practice mindfulness to assist remind them to be mindful in living their lives and not be enthralled by the joys of various sorts of defilements if they don’t want to lose out on significant times in their lives. Because one will become aware of the value of one’s own life, the lives of others around him, and the significance of health when living carelessly in every minute of the mind as if death is just around the corner. perhaps all of one’s wealth is really an illusion. They will eventually pass away because it is all so fleeting, and death will act as a wake-up call for us to get back to the essentials and the truth. A daily practice of death mindfulness can help one get closer to the true meaning of existence by letting go of the outer, temporary shell that is life. Living carelessly is defined as not being vigilant and aware of developments at all times. Someone constantly faces death and is not horrified when it occurs.